The Oxford handbook of management consulting - Kipping, Matthias; Clark, Timothy, 1964- (Oxford : Oxford University Press, 2012)
Management consultants of various kinds play an important role in the world of business, and other organizations. This handbook provides a comprehensive overview of research and thinking on the role, history, and function of management consultants.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Business consultants -- Handbooks, manuals, etc